Soil type and land-use patterns determine the composition of canonical ammonia oxidizers and comammox Nitrospira communities - Xinli Wang; Fei Zhu; Chi Zhang; Jiaxing Wei; Yongquan Shang; Bo Liu; Yun Wang (Applied Soil Ecology, 2026)

Different green manures showed inconsistent effects on soil properties, fungal communities and crop yield - Chenxin Wei; Zihan Hu; Yutong Jiang; Buyun Zhou; Zilong Hu; Guilong Li; Li Wan; Xingjia Xiang; Jia Liu (Journal of Soils and Sediments, 2026)

Analytical Solutions for the Consolidation of Composite Ground Improved with T-Shaped Deep Mixing Piles Considering Pile Penetration Deformation - Mingyuan Wang; Lili Wang; Haofeng Xing; Hongbo Chen (Geotechnical and Geological Engineering, 2026)

Soil compaction alters soil aeration and promotes arsenic accumulation in wheat at the seedling stage in a clay loam Alfisol - Xin-Jun Huang; Lan-Ting Liu; Li-Ping Li; Yong-Qiang Yang; Ya-Li Wang; Rainer Horn; Stephan Peth (Plant and Soil, 2026)

Chiglitazar alleviates cognitive dysfunction in diabetic mice by restoring mitochondrial function via the PPARs/Nrf2 signaling pathway - Junfang Yuan; Yuzhong Wang; Defeng Wang; Yanfeng Zhen; Yanan Sun; Li Wang; Hui Fang (Metabolic Brain Disease, 2026)

Luteolin ameliorates sympathetic stress-induced myocardial injury by inhibiting the VEGFA/VEGFR2 and PI3K/Akt/NF-kappaB signaling pathways - Sheng Li; Yanli Guo; Peiyao Yang; Yaming Liu; Xinzhi Li; Ketao Ma; Li Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The characteristics and expression profile of follicle‐stimulating hormone and luteinizing hormone during gonadal development in silver pomfret - Chunyang Guo; Dingyuan Zhang; Yi Wang; Xubo Wang; Shanliang Xu; Danli Wang (Journal of Fish Biology, 2026)
The hypothalamic–pituitary‐gonadal (HPG) axis, particularly follicle‐stimulating hormone (Fsh) and luteinizing hormone (Lh), is essential for the regulation of teleost reproduction. However, their expression dynamics and receptor distribution during gonadal development in silver pomfret remain poorly understood. This study aimed to characterize the expression profiles and cellular localization of Fshβ, Lhβ and their receptors (Fshr and Lhr) in the pituitary and gonads and to evaluate their potential roles in reproductive regulation. The different staining method and transmission electron microscopy (TEM) were used to analyse the structural changes of the pituitary gland during the reproductive season. Quantitative PCR (qPCR) and immunohistochemical (IHC) were used to detect the expression pattern of Fshβ and Lhβ. The results showed that the number of endocrine granules significantly increased before the reproductive season, and their electron density intensified. During the spawning season, the secretory granules gradually depleted, leading to the appearance of vacuolization. In the pituitary gland, the expression of fshβ in Stage IV was significantly higher in the female pituitary, but significantly higher in Stage V in the male. Fshβ and Lhβ signals were mainly located in the proximal pars distalis (PPD) and pars intermedia (PI) regions of the pituitary. In the gonad, Fshr signals were observed in the spermatogonia type A cells and Sertoli cells in testes, whereas Lhr signals were observed in spermatogonia and secondary spermatocytes in the testes. Fshr and Lhr signals were both observed in the follicle cells surrounding the oogonia and vitellogenic oocytes in the ovary of silver pomfret. The expression patterns of fshβ and fshr were essentially similar after different hormone treatments in the gonad and methyltestosterone (MT) could influence the expression of fshβ , lhβ and fshr in the testis. Taken together, our data suggest that Fshβ and Lhβ promote the development and maturation in the gonad, and Fshr and Lhr may be involved in ovary maturation and spawning.

Research on the mechanism of Eucalyptus tannins inhibiting soil respiration - Xinya Li; Miaoling Wang; Gairen Yang; Zhifeng Xie; Shiqi Wei; Lisha Li; Yusong Deng; Huili Wang (Applied Soil Ecology, 2026)

Effects of silver nanoparticles and nitrile fungicides on soil microbial community structure, metabolic functions, and resistance genes - Yiwang Wang; Ting Gao; Jiajia Liu; Shaoheng Bao; Fuli Wang; Ge Yao; Xiaoyan Lin; Shijie Jiang; Jinlong Lai; Penggang Han; Jiang Hui (Applied Soil Ecology, 2026)

In Vitro Antibacterial Activity of Glutathione Against Aeromonas veronii and Its In Vivo Effects on Intestinal Microbiota in Koi Carp ( Cyprinus carpio Var. koi ) - Haoyue Zhang; Jingfeng Sun; Zhuoran Han; Anli Wang (New Zealand Journal of Marine and Freshwater Research, 2026)
Aeromonas veronii is a pathogenic bacterium that threatens freshwater fish, including koi carp. Antibiotics used to control bacterial infections can disrupt the intestinal microbiota and promote antibiotic resistance. This study aimed to evaluate the in vitro antimicrobial activity of glutathione (GSH) against A. veronii and its impact on the intestinal microbiota of koi carp. To this end, we examined bacterial growth, biofilm formation, and motility of A. veronii . We further analyzed the intestinal microbiota composition by 16S rRNA high‐throughput sequencing and assessed disease resistance in koi carp after 7 days of dietary GSH supplementation. The results showed that GSH inhibited A. veronii growth, biofilm formation, and motility, with stronger effects at higher doses. GSH supplementation also significantly altered the intestinal microbiota, reducing potential pathogenic bacteria like Aeromonas and promoting beneficial ones. Moreover, GSH enhanced disease resistance, with treated fish showing lower cumulative mortality compared to controls. However, the GSH doses of 720 mg/kg caused hepatic burden, emphasizing the need for careful dose optimization. These findings highlight the significance of GSH in modulating the intestinal microbiota of fish, a process that may contribute to enhanced disease resistance, and emphasize the importance of optimizing its dosage for safe application in aquaculture.

Eucalyptus residues derived biochar rather than direct return in maintain soil bacterial communities structure and functions - Chenji Li; Josep Peñuelas; Lijun Chen; Guowei Liang; Huili Wang; Jizhao Cao; Jia Lu; Lichao Wu (Applied Soil Ecology, 2026)

Different responses of soil bacterial necromass carbon and fungal necromass carbon to nitrogen deposition in meadow steppe - Na Jiang; Hao Zhang; Siyu Zhang; Jie Qin; Hui Wang; Yanjun Zhang; Dianlin Yang; Lili Wang; Qiannan Yang; He Ye; Mei Hong; Haifang Zhang (Applied Soil Ecology, 2025)

Plant above-ground biomass drives the recovery of soil microbial communities in a subtropical-temperate transition zone following forest wildfire - Mengjun Hu; Jiayin Feng; Yu Shi; Pengshuai Shao; Zhijie Chen; Zhenxing Zhou; Jiali Wang (Applied Soil Ecology, 2025)

Group behaviors and dynamics of plant-parasitic nematodes: Aggregation, clumping and their implications - Dan Jiang; Congli Wang; Xuemei Niu; Ye Jiang; Minghui Huang; Chunjie Li (Applied Soil Ecology, 2025)

Enhancing the immobilization efficiency of mercapto-palygorskite on soil Cd through earthworm addition: Cd fractions, soil aggregates, and bacterial community - Yale Wang; Kaihui Hou; Junxiao Jiang; Xu Gao; Yingming Xu; Yali Wang; Chunhong Xu; Liping Li; Xuefeng Liang; Gaoling Shi (Applied Soil Ecology, 2025)

Microbial dynamics and agroforestry impact on soil ecosystem multifunctionality following forest conversion to macadamia-based systems - Fandi Xu; Zhihong Guo; Yuchun Yang; Yanxuan Chen; Haidong Bai; Tongli Wang; Jiangchong Wu; Shuaifeng Li; Jianrong Su (Applied Soil Ecology, 2025)

Successive monoculture of Eucalyptus spp. alters the structure and network connectivity, rather than the assembly pattern of rhizosphere and bulk soil bacteria - Huili Wang; Zhengye Wang; Qiyun Qin; Qin Ke; Lijun Chen; Xianchong Song; Xiaolong Chen; Lichao Wu; Jizhao Cao (Applied Soil Ecology, 2024)

Impacts of fire on soil respiration and its components: A global meta-analysis - Haoran Gui; Jiali Wang; Mengjun Hu; Zhenxing Zhou; Shiqiang Wan (Agricultural and Forest Meteorology, 2023)

Predicting temperature and rainfall for plantation forestry in Mpumalanga, South Africa, using locally developed climate models - Jaco-Pierre van der Merwe; Tongli Wang; Charlie Clarke; Shawn D. Mansfield (Agricultural and Forest Meteorology, 2023)